Crystallinity, morphology and high dielectric permittivity of NiO nanosheets filling Poly(vinylidene fluoride) - Amoresi, Rafael A. C. [UNESP]; Felix, Anderson A. [UNESP]; Botero, Eriton R.; Domingues, Nelson L. C.; Falcao, Evaristo A.; Zaghete, Maria A. [UNESP]; Rinaldi, Andrelson W. (Elsevier B.V., 2015)
Composite films based on Poly(vinylidene fluoride) (PVDF) polymer filled with Nickel oxide (NiO) nanosheets were prepared via the solution casting method. The effect of NiO filler introduction on the structure and morphology of the composite films were analyzed by X-ray diffraction, Fourier transformed infrared spectroscopy and Scanning Electron Microscopy. The results showed that the crystallinity, beta-phase content and morphology are directly related to the NiO filler concentration into the polymer matrix owing to a heterogeneous nucleation. Electrical measurements revealed dielectric constants up to 45 at 1 kHz and an increasing in conductivity more than two orders of magnitude, with a percolation threshold of about 4.0% v/v of NiO filler content. (C) 2015 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Powders: chemical preparation; Composites; Dielectric properties; Functional applications